PHILOSOPHY AND ITS INTERCONNECTION WITH SCIENCE AND THE HUMANITIES - Shahnoza Isroilova (Web of Journals Publishing, 2025)
In this paper we will attempt to determine the essence of philosophical thinking with respect to a closely- related form of spiritual culture – scientific knowledge. The purpose of the study is to identify the possibility or impossibility of defining philosophy as one of the sciences belonging to the humanitarian sphere. The pro arguments of the scientific status of philosophy and the arguments rejecting the possibility of defining philosophy as a science are discussed. Nevertheless, philosophy per se is significantly wider than its purely scientific segment, creating fundamentally new ways of understanding reality, and thereby leaving the limits of concrete scientific knowledge.
Keywords: Criteria of scientific content, humanities, philosophy, science.